Mandatory retirement savings in private sector: category of employees required to contribute - Ali Mohamed, Ashgar Ali (LexisNexis Malaysia Sdn Bhd, 2019)
This article discusses on the compulsory retirement savings under the Employees Provident Fund Act 1991 with special focus on the categories of employees that are required to make contributions thereto.